A novel Z-scheme heterojunction photocatalyst CeO2@WO3 nanocomposite with enhanced visible-light photocatalytic performance for wastewater treatment by cephalexin antibiotic degradation: Process optimization - Wang, Shuaibing; Liu, Junhong; Albaijan, Ibrahim; Shawabkeh, Ali; Lin, Haitao; Ahmad, Irfan; Rab, Safia Obaidur; Alshahrani, Mohammad Y. (Journal of industrial and engineering chemistry (Seoul, Korea), 2024)
[Display omitted] Considering growing global environmental concerns, there is a heightened focus on expediting the synthesis of highly efficient catalytic materials to address these challenges effectively. Herein, a novel CeO2@WO3 heterojunction photocatalyst was synthesized using an ultrasonic-assisted method for the environmentally friendly degradation of cephalexin (CPX) under visible light. The optimized photocatalyst synthesis condition was achieved by assessing the influence of effective parameters, including the CeO2 content (5–25 wt%) and calcination temperature (300–600 °C), employing the RSM method. The synthesized photocatalysts were comprehensively characterized through XRD, SEM, TEM, EDS-mapping, BET, FTIR, and UV–Vis band gap analysis. Using optimal photocatalyst (CeO2 content: 15.78 %, calcination temperature: 440.59 °C, and ultrasonic power: 80 W), the influence of four critical variables on CPX degradation was thoroughly investigated via RSM-CCD. The maximum CPX degradation efficiency of 98.8 % was attained under the following optimal conditions: CPX concentration: 20.00 mg/L, solution pH: 6.79, photocatalyst dosage: 0.019 g/L, and visible light time: 94.82 min. Statistical analysis confirmed the accuracy of the regression model based on empirical data. The CeO2@WO3 heterojunction demonstrated substantial Chemical Oxygen Demand (COD) removal, reaching 73.26 % during the mineralization of CPX, surpassing the outcomes of previous studies. Trapping experiments and EPR analysis indicated the crucial involvement of hydroxyl radicals and superoxide radicals as highly active species due to their non-selective oxidation capabilities. Furthermore, a Z-scheme charge transfer mechanism was proposed to elucidate the enhanced photocatalytic activity. Identifying degradation intermediates was accomplished through HPLC-MS analysis, leading to a plausible pathway for CPX degradation. Overall, CeO2@WO3 exhibited excellent stability and could endure five cycles with minimal cerium leaching, highlighting its effectiveness in decomposing organic contaminants.